2004
DOI: 10.4054/demres.2004.s3.3
|View full text |Cite
|
Sign up to set email alerts
|

Value Orientations and the Second Demographic Transition (SDT) in Northern, Western and Southern Europe: An Update

Abstract: This special collection is in honor of Jan M. Hoem on his 65 th birthday. The authors presented their papers at a working party at the Max Planck Institute for Demographic Research in Rostock, Germany in April 2004. The collection is edited by Gunnar Andersson and Gerda Neyer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
267
0
39

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(313 citation statements)
references
References 19 publications
7
267
0
39
Order By: Relevance
“…Finally, we account for religiosity, which has been shown to influence both family demographic behavior and the relative timing of family life events (Surkyn & Lesthaeghe, 2004).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Finally, we account for religiosity, which has been shown to influence both family demographic behavior and the relative timing of family life events (Surkyn & Lesthaeghe, 2004).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Isso porque os grupos -ou domicílios -à frente nessa transição tendem a adotar novos conjuntos de preferências e estilos de vida, nos quais existe aumento no consumo de bens não duráveis, configurando um padrão potencializador da geração de resíduos sólidos domiciliares. Este argumento é abordado direta ou indiretamente por Fernández-Villaverde e Krueger (2001), Surkiyn e Lesthaeghe (2004) …”
Section: Análise De Clustersunclassified
“…One element that may be particularly relevant in this respect is exposure to the behaviour in question. First, approval of a certain type of behaviour is more likely if a person has expressed that behaviour him or herself (Surkyn and Lesthaeghe 2004). Trent and South (1992) and Gelissen (2003) found that persons who are divorced hold more liberal attitudes towards divorce.…”
Section: Country-level Determinantsmentioning
confidence: 99%